Shuxie-1 Decoction Alleviated CUMS -Induced Liver Injury via IL-6/JAK2/STAT3 Signaling - Mengting Zhang; Wanhong Wu; Wanhong Wu; Caoxin Huang; Teng Cai; Nengjiang Zhao; Suhuan Liu; Shuyu Yang (Frontiers Media S.A., 2022)
Introduction: Chronic stress has been shown to cause liver damage in addition to psychological depression. Besides, drug-induced liver injury is frequently caused by antidepressants. Shuxie-1 decoction (SX-1) is a formula of traditional Chinese medicine commonly used in nourishing liver blood, and relieving depression. However, the underlying molecular mechanism remains unclear. Therefore, this study was designed to explore the effects and mechanisms of SX-1 in treating chronic stress-induced depression as well as liver injury.Methods: Chronic unpredictable mild stress (CUMS) was applied to male Wistar rats for 4 weeks, with or without administration of SX-1 at low-dose and high-dose for 6 weeks, using Fluoxetine (Flu) as a positive control. Body weight was monitored once every 2 weeks. In the sixth week, the sugar preference test and open field test were carried out to evaluate the depression status. After that, the serum and liver tissues were collected. The quality control of SX-1 decoctions and drug-containing serum was controlled by UHPLC-QE-MS. The cell viability was measured by Cell Counting Kit-8 (CCK8). Enzyme-linked immunosorbent assay (Elisa), Western Blot and immunohistochemistrical staining was obtained to detect the protein levels in the plasma and the hepatic tissues, respectively.Results: CUMS led to decreased 1) body weight, 2) the preference for sugar water, 3) the desire to explore in open field, and increased serum levels of corticosterone. All these factors were completely reversed by SX-1 treatment. Hematoxylin-eosin staining (HE) showed that SX-1 improved the hepatocyte vacuolization in CUMS treated rats, decreased the serum levels of alanine aminotransferase (ALT) and the deposition of type I collagen (Col I) in hepatocytes as well. CUMS increased the levels of hepatic Interleukin-6 (IL-6), and provoked the activation of Janus kinase 2 (JAK2) and signal transducer and activator of transcription 3 (STAT3), which was abrogated by SX-1 treatment. Cobalt chloride (CoCl2) increased the protein expression of IL-6 and p-STAT3 in AML12 cells. Besides, nuclear pyknosis was observed under electron microscope, which were recovered after rat SX serum.Conclusion: SX-1 effectively ameliorated CUMS-induced depression-like behaviors as well as hepatic injuries, probably by the blockade of hepatic IL-6/JAK2/STAT3 signaling.